# iii. Simplify (3/5 + 2/7) – (3/7 + 2/5)

## Answers

Answered by

1

**Answer:**

2/35

**Step-by-step explanation:**

=[(3×7+5×2)/35]-[(3×5+2×7)/35]

=(21+10)/35]-[(15+14)/35]

=(31-29)/35

=2/35

Answered by

3

**Answer:**

3/5+2/7 - 3/7-2/5(because if we open bracket sign will also change)

3/5-2/5+2/7-3/7 (we can now change position in equation)

1/5-1/7 (the all are like terms and its your solution.)

**Step-by-step explanation:**

3/5+2/7 - 3/7-2/5

3/5-2/5+2/7-3/7

1/5-1/7

Similar questions